2016
DOI: 10.3325/cmj.2016.57.180
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants selenomethionine and D-pantethine decrease the negative side effects of doxorubicin in NL/Ly lymphoma-bearing mice

Abstract: AimTo investigate the potential tissue-protective effects of antioxidants selenomethionine and D-pantethine applied together with doxorubicin (Dx) on NK/Ly lymphoma-bearing mice. The impact of this chemotherapy scheme on animal survival, blood cell profile, hepatotoxicity, glutathione level, and activity of glutathione-converting enzymes in the liver was compared with the action of Dx applied alone.MethodsThe hematological profile of animals was studied by the analysis of blood smears under light microscopy. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…NK/Ly lymphoma growth induced leukocytosis in the tumor-bearing mice that was well seen on the 21 st day after tumor inoculation. All agents used in this study -Les-3833 and Les-3288 compounds and doxorubicin (positive control) -significantly decreased tumorinduced leukocytosis, and a similar character of action was characteristic for segmented nuclei leukocytes and ring-shaped nuclei leukocytes as indicators of tissues damage [21,22]. However, tumor growth was shown to decrease significantly the number of small lymphocytes which provide protection against the action of antigens and toxic agents.…”
Section: Discussionmentioning
confidence: 56%
“…NK/Ly lymphoma growth induced leukocytosis in the tumor-bearing mice that was well seen on the 21 st day after tumor inoculation. All agents used in this study -Les-3833 and Les-3288 compounds and doxorubicin (positive control) -significantly decreased tumorinduced leukocytosis, and a similar character of action was characteristic for segmented nuclei leukocytes and ring-shaped nuclei leukocytes as indicators of tissues damage [21,22]. However, tumor growth was shown to decrease significantly the number of small lymphocytes which provide protection against the action of antigens and toxic agents.…”
Section: Discussionmentioning
confidence: 56%
“…We conducted studies using mice with NK/Ly lymphoma and showed that these dietary supplements, besides lowering the myelotoxicity of Dx, also lead to a boost of survival time of tumor-bearing animals (11). One of the aims of present study was to verify those data using more aggressive solid tumor model – murine B16 melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Нещодавно встановлено, що антиоксиданти (селенометіонін -SeMet і D-пантетин -D-Pt) проявляють нефро-, мієло-та гепатопротекторну активність щодо мишей-пухлиноносіїв, лікованих традиційним протипухлинним препаратом доксорубіцином (Dx). Крім того, ці антиоксиданти пригнічують цитотоксичний ефект Dx щодо чутливих до хіміотерапії пухлинних клітин і посилюють ефект препарату щодо певних стійких до хіміотерапії пухлинних клітинних ліній (HL-60/vinc, HL-60/adr), тоді як для інших резистентних клітинних ліній (HCT-116/Bax(−/−), HCT-116/p53) такий феномен ми не спостерігали [14][15][16][17].…”
Section: антиоксиданти селенометіонін і D-пантетин впливають диференцunclassified
“…It was found that antioxidant supplements possess nephro-, myelo-and hepatoprotective activity toward doxorubicin (Dx) action on the organism of tumor-bearing mice. Also, these antioxidants partially sensitized drugresistant tumor cells toward cytotoxic action of the doxorubicin (Dx) [15][16][17]. However, the molecular mechanisms underlying such effects of selenomethionine and D-pantethine remain unexplored.…”
Section: Introductionmentioning
confidence: 99%